Cognition Is Associated With Peripheral Immune Molecules in Healthy Older Adults: A Cross-Sectional Study - Serre-Miranda, Cláudia; Roque, Susana; Santos, Nadine Correia; Costa, Patrício; Sousa, Nuno; Palha, Joana Almeida; Correia-Neves, Margarida (Frontiers in Immunology, 2020)
Background. Cognition in the elderly is heterogeneous. Senescence of the immune system is increasingly considered as a potential player in cognitive performance. We explore here the interplay between cognitive performance and peripheral immune molecules in healthy older individuals. Methods. Cross-sectional study of clinically well characterized senior healthy cohort (120 participants; 51 to 87 years old) previously clustered as “Good” and “Poor” performers based on well-established tests that evaluate memory and executive function. Plasma concentration of 30 immune molecules was assessed by multiplex analysis and correlated with parameters of cognitive performance. Results. Participants with worst cognitive performance (“Poor”) presented increased concentrations of IL-1b, IL-8, IL-13 and TNF when compared to individuals with a better cognitive performance (“Good”). The cognitive dimensions memory and executive function, when considered separately, presented a negative association with several immune molecules (IL-1b, IL-1RA, IL-6, IL-13, IP-10 and TNF with memory and only IL-1b with executive function), even controlling for age, sex, years of formal education, mood and use of anti-inflammatory drugs. Regression analysis showed that several of these molecules (IL-1b, IL-6, IL-8 and IL-13) contribute to predict whether an individual belongs to the “Good” or “Poor” cognitive performance group. Conclusions. These results strength the association between increased concentration of peripheral immune molecules, like IL-1b, and worse cognitive performance in senior healthy individuals. In addition, the broad spectrum of molecules analyzed revealed IL-13 as a new player on these interaction.